Can Liquefaction Be Repeated? An Electrical Resistivity Study at South Palu, Indonesia - Satiawan, Soni; Hadad, Dhani Ahmad; Saragih, Donar (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
The recurrence of liquefaction remains a significant concern, prompting a resistivity study in South Palu to investigate subsurface condition associated with this phenomenon. A total of eight lines 2D resistivity lines with dipole-dipole configuration and 10m electrode spacing were acquired in the South Palu subdistrict, covering a cumulative length of 1470m. All stages of data processing and modelling were conducted using a regularized inversion algorithm implemented in the Phyton-based ResIPy software. The inversion results revealed three distinct resistivity layers, low-resistivity ranging from 4.1 – 78.5 ohm.m, interpreted as low permeability a sandy shale or clay rich soil with saturated clay layer extending to a depth of approximately 10m, an underlying high-resistivity layer ranging from 78.6 - 201.4 ohm.m, interpreted as a saturated sand or gravel layer with ± 10m of thickness and associated as a good aquifer and the deep layer at ±20 m depth with highest resistivity (> 200 ohm.m) which is interpreted as compacted sand or hard soil and acted as the base soil in this study area. The evidence of sand intrusion features, upward – moderate to high resistivity intrusions, potentially associated with liquefaction events, were observed in six of resistivity sections. These are indicated by the upward penetration of moderate to high-resistivity value through the low-resistivity layer, towards the surface. Additionally, the recurrence of liquefaction is still conceivable since the existence of ±10m of layer-2 which is interpreted as the most potential liquefiable layer and the thickness of low resistivity of layer-1 and in study area, particularly if subjected to strong earthquake motion.